Large airway ventilatory functions in female patients of rheumatoid arthritis with methotrexate therapy- is there any change? - Yasmin, Fatema; Begum, Shelina (Journal of Bangladesh Society of Physiologist, 2018)
Background: Methotrexate (MTX) is widely used in the treatment of Rheumatoid arthritis (RA) as first line disease modifying anti-rheumatoid drug. Low dose MTX may reduce lung function status in RA patients. Objective: To observe the changes in large airway ventilatory variables in RA patients after MTX therapy. Methods: For this prospective observational study, 24 female RA patients of age ranges between 15 to 65 years were selected from the Out-Patient Department of Rheumatology, Bangabandhu Sheikh Mujib Medical University, Dhaka. Age and BMI matched 24 apparently healthy females were also selected Control. To assess the large airway ventilatory function, FVC, FEV1, FEV1/ FVC% and PEFR of all subjects were measured with a portable digital Spirometer, PONY FX (Cosmed, Italy) at Day 0. In addition, all these variables were again measured in the RA patients after 180 days of MTX therapy. For statistical analysis, independent sample t test and paired sample t test were performed. Results: All the study variables (except FEV1/FVC%) were significantly (p<0.001) lower in RA groups at day 0 as well as at day 180, compared to healthy controls. Again all these variables were almost similar in the RA patients at day 180 when compared to those of day 0. Conclusion: Large airway ventilatory function deteriorated in RA patients, which may not be recovered by six months methotraxate therapy. J Bangladesh Soc Physiol. 2018, June; 13(1): 35-40